1984
DOI: 10.1093/nar/12.21.8161
|View full text |Cite
|
Sign up to set email alerts
|

In vitroevidence that eukaryotic ribosomal RNA transcription is regulated by modification of RNA polymerase I

Abstract: We have utilized a cell-free transcription system from Acanthamoeba castellanii to test the functional activity of RNA polymerase I and transcription initiation factor I (TIF-I) during developmental down regulation of rRNA transcription. The results strongly suggest that rRNA transcription is regulated by modification, probably covalent, of RNA polymerase I: (1) The level of activity of TIF-I in extracts from transcriptionally active and inactive cells is constant. (2) The number of RNA polymerase I molecules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0

Year Published

1986
1986
1996
1996

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 32 publications
(20 reference statements)
4
36
0
Order By: Relevance
“…When this occurs, rRNA transcription, which in the proliferating cell is 75% of pulse-labeled RNA, ceases completely ( Fig. 1) (23,27). We show here that 5S RNA transcription is coordinately modulated with rRNA.…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…When this occurs, rRNA transcription, which in the proliferating cell is 75% of pulse-labeled RNA, ceases completely ( Fig. 1) (23,27). We show here that 5S RNA transcription is coordinately modulated with rRNA.…”
mentioning
confidence: 56%
“…When cells are transferred to starvation medium, they leave the growth/division cycle and begin differentiation into dormant cysts. In the early stages of this process, rRNA transcription is shut off (4,23,27) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This activity loss could be reproduced with purified components, and it was shown that it was the polymerase fraction that lost activity when A. castellanii entered stationary phase. Pol Is purified from growing cells or cysts differed in their abilities to specifically initiate rDNA transcription (2,32). In addition, both enzymes had different heat stabilities, a finding which suggested that Pol I itself was modified (32).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in apparent analogy to the loss of factor C activity in growth-arrested mammalian cells, encysting cells of the soil amoeba Acanthamoeba castellandi also demonstrate downregulation of rRNA gene transcription as a result of loss of specific initiation competence by the RNA polymerase I (1,48). No specific initiation factor has been separated from the A. castellandi RNA polymerase I catalytic activity, but the A. castellanii RNA polymerase I (which has twice as many copurifying polypeptides as does the mammalian enzyme) could bind its C* equivalent more tightly.…”
Section: -Nt)mentioning
confidence: 99%